Translation, cultural adaptation and validation of the DASH - upper extremity functional scale - García González, Luis Alejandro; Aguilar Sierra, Francisco Javier; Moreno Serrano, Constanza; Enciso, Mónica (Revista Colombiana de Ortopedia y Traumatología, 2017)
Introduction: The objective of the study was to perform translation, cultural adaptation and validation of a function scale of the upper limb, called DASH, for its acronyms in English (disability of the arm, shoulder and hand). Materials and methods: A methodological study of scale validation was performed: translation (consisting of English-Spanish translations, initial expert committee, two backtranslations, a second committee of experts and a definitive translation); reliability assessment (internal consistency tests, test-retest and minimum detectable change); response to change (measurements in patients before and after treatment), and validity study (validity tests of appearance, construct and criteria were performed). Results: The translated test was applied to 338 patients with hand and shoulder diseases, 311 were usable. The internal consistency, using Cronbach’s alpha, was estimated to be > 0.96; The result of the Lin coefficient of agreement was 0.86. The minimum detectable change was 15.88, the ability to respond to change using the Student t test applied on the difference in score yielded a p <0.001; A nonparametric Spearman correlation was recorded between the difference in the DASH score and the difference in the visual analogue scale of change in health status (EVA HEALTH) with r = 0.62 (p <0.001). Discussion: The DASH scale, translated and adapted to Spanish demonstrated good reliability, stability and responsiveness to change, managed to discriminate between different diseases and has an estimated validity in terms of content, construct and criteria. Level of clinical evidence: Level II.